Video Game Genre, Evolution and Innovation - Arsenault, Dominic (Eludamos: Journal for Computer Game Culture, 2009)
This paper provides a critical overview of the notion of genre in game studies and in the video game industry. Using the concept of genre requires one to acknowledge the recent developments of genre theory in other fields of research; one such development is the contestation of the idea of generic evolution. After a comparative analysis, video game genres are found to differ from literary and film genres precisely on the basis of evolution. The technological imperatives that characterize video game production are also pinpointed as relevant to the establishment and development of video game genres. Evolution is linked to the processes of innovation, and so a model of innovation is laid out from a compare-and-contrast approach to literary and film genre innovation. This model is tested through the history and analysis of the First-Person Shooter genre. This results in new insights for the question of genre in video games, as it is established that genre is rooted not in game mechanics, but in game aesthetics; that is, play-experiences that share a phenomenological and pragmatic quality, regardless of their technical implementation.